Development of a Spark-Detection System for the Quality Assurance of Large-Area GEM-Foils. (April 2020) - Ball, M; Block, T; Hauer, P; Ottnad, J; Urban, S; Ratza, V; Ketzer, B
Abstract: Gaseous detectors based on large-size GEM-foils are planned to be used for a variety of upgrades and new experiments using high-rate and high-intensity particle beams. An excellent quality control of GEM-foils is a mandatory prerequisite to select the best foils for the assembly of a GEM detector. The high voltage stability of the foils is here of uppermost importance. In particular discharges that occur at the same position need to be detected. A spark detection system has been developed to automatically detect and record the time and position of sparks. The system is based on a commercial web camera installed in a housing for the tests and a custom-made, LabVIEW-based software for control and operation. An automatic Spark-Detection System for GEM foils was designed, built and characterized. It is able to detect and record discharges in large-size GEM foils during the quality control procedure. The spark detection e ciency was estimated to be higher than 97 %, the position resolution was determined to be approximately 0.5 mm. With this system, the characterization of GEM foils can be standardized to a much greater degree than before.